Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai Dinas Perindustrian Perdagangan Energi dan Sumber Daya Mineral Provinsi Sumatera Utara - Muhammad Rafly Syuhada; Ananda Fitriani Dewi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The phenomenon that occurs in this study is the lack of motivation or encouragement provided by the boss which results in employees not being optimal in achieving the work targets that have been set by the company. So that the role of superiors is very necessary in terms of motivation such as promotion, giving awards, and enthusiasm to build employee morale in doing work. The purpose of the study is to find out partially and simultaneously the relationship between work motivation variables and work discipline that affect employee performance. The type of research method used is a quantitative method with a saturated sample sampling technique. The findings in this study are (1) obtained a motivation calculation t value of 3.546 > ttable 2.003 with a Sig probability of 0.000 < 0.05 then motivation has a positive and significant effect on Employee Performance, (2) a discipline calculation t value of 2.574 > ttable 2.003 with a Sig probability of 0.022 > 0.05, then discipline has a positive but not significant influence on Employee Performance at the Department of Industry, Energy and Mineral Resources Trade North Sumatra Province.